2023
DOI: 10.3390/genes14030766
|View full text |Cite
|
Sign up to set email alerts
|

Floral Development Stage-Specific Transcriptomic Analysis Reveals the Formation Mechanism of Different Shapes of Ray Florets in Chrysanthemum

Abstract: The formation mechanism of different ray floret shapes of chrysanthemum (Chrysanthemum × morifolium) remains elusive due to its complex genetic background. C. vestitum, with the basic ray floret shapes of the flat, spoon, and tubular types, is considered a model material for studying ray floret morphogenesis. In this study, the flat and tubular type lines of C. vestitum at specific stages were used to investigate the key genes that regulate morphological differences in ray florets. We found that the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…It has been shown that miRNA164 acts in conjunction with NAM/CUC as a homeostatic mechanism to regulate auxin signaling [ 27 , 29 , 30 ], while the localized enrichment of auxin is essential for floret patterning in Asteraceae [ 31 ]. In addition, auxin also has a regulatory role in the corolla morphology of ray floret in chrysanthemums [ 32 , 33 ]. In the present study, many differential expressions of auxin transporter proteins and auxin response factors were found in the OE- ClNAM lines, suggesting that cla-miR164- ClNAM may affect inflorescence architectures in chrysanthemums by regulating auxin signaling ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miRNA164 acts in conjunction with NAM/CUC as a homeostatic mechanism to regulate auxin signaling [ 27 , 29 , 30 ], while the localized enrichment of auxin is essential for floret patterning in Asteraceae [ 31 ]. In addition, auxin also has a regulatory role in the corolla morphology of ray floret in chrysanthemums [ 32 , 33 ]. In the present study, many differential expressions of auxin transporter proteins and auxin response factors were found in the OE- ClNAM lines, suggesting that cla-miR164- ClNAM may affect inflorescence architectures in chrysanthemums by regulating auxin signaling ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the morphological differences among various inflorescence and petal forms, a total of 12 chrysanthemum cultivars in five categories were observed at the full-bloom stage. As mentioned above, the classification of petal types is often based on the CTMD [9,10]. Generally speaking, the larger the merged degree, the more tubular the petals and the smaller the merged degree, the flatter the petals [9].…”
Section: Morphological Observations Of Different Inflorescence Forms ...mentioning
confidence: 99%
“…Moreover, the expression patterns of essential candidate genes, such as ClPIN1, ClARF5, CmYAB1, and CmCYC2s etc., were verified by RT-PCR and RNA in situ hybridization [14][15][16]. In recent years, the CYC-like TCP domain proteins have become a research hotspot for floret development in Asteraceae [10]. The CYC group experienced repetition and generated three main groups: CYC1, CYC2, and CYC3 [17].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation